2023
DOI: 10.1093/eurpub/ckad073
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy among first-generation immigrants living in Sweden

Abstract: Background In many countries, immigrants face higher risks of contracting and dying from COVID-19 compared with the native-born population. Moreover, their COVID-19 vaccination uptake tends to be lower. This study aimed to investigate COVID-19 vaccine hesitancy in relation to sociodemographic characteristics, COVID-19-related exposures and social values, norms and perceptions among first-generation immigrants in Sweden. Vaccine hesitancy is an important public health issue to ensure protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The first determinant variable was sex. In contrast to the findings of Gram et al [21] (similar vaccination coverage between sexes), Bastola et al [18] (lower vaccine uptake in males from the total sample), and Page et al [28] (increased female willingness to be vaccinated), female immigrants were generally more hesitant and/or opposed to vaccination than male immigrants [16,19,22,25,27,29,30]. We believe that this female attitude may be influenced by a greater attachment to the culture of the country of origin, and, consequently, immigrant women have a greater fear/suspicion of accepting directions from the institution in the host country.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The first determinant variable was sex. In contrast to the findings of Gram et al [21] (similar vaccination coverage between sexes), Bastola et al [18] (lower vaccine uptake in males from the total sample), and Page et al [28] (increased female willingness to be vaccinated), female immigrants were generally more hesitant and/or opposed to vaccination than male immigrants [16,19,22,25,27,29,30]. We believe that this female attitude may be influenced by a greater attachment to the culture of the country of origin, and, consequently, immigrant women have a greater fear/suspicion of accepting directions from the institution in the host country.…”
Section: Discussionmentioning
confidence: 60%
“…Specifically, five of these were carried out in Norway, two each in France, Germany, and Italy, one each in Finland, Denmark, Sweden, and Turkey, and one multicentric study in Switzerland, France, and Italy. Three studies (19%) were published in 2021 [23,25,29], four (25%) in 2023 [16,18,21,30], and the remaining nine studies (56%) in 2022 [17,[19][20][21][22]24,[26][27][28]. The earliest data collection was compiled in the period May 2020-June 2020 in Longchamps' study [25], which investigated the hesitancy to vaccinate, as the COVID-19 vaccine was not yet available; the latest one was compiled on COVID-19 vaccination status in February, March, and May 2022 by Aysit et al [16].…”
Section: Overview Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Contributing factors to vaccine hesitancy were misinformation, lack of knowledge, safety concerns, personal beliefs, language barriers, immigrant status, and vaccine access. Moreover, most of the studies presented interesting perspectives on vaccine hesitancy, including "social stigma", "loss of autonomy", "fatalism", "immigration status", "parental consent", "old age", and "lack of formal education" [12,20,21,23,24,27,29,[31][32][33]37,[39][40][41].…”
Section: Challenges Opportunities and Lessons Learnedmentioning
confidence: 99%
“…The WHO has implemented the Immunization Agenda 2030, a global strategy to maximize the impact of vaccines and save 50 million lives over the next decade [2]. However, some studies have shown disproportionate mortality rates and lower vaccine uptake among immigrant populations [12]. According to Guttmann et al, 2020 [8], nearly half (43.5%) of total COVID-19 cases in Canada involve immigrants although their immigrant population only makes up a quarter (25%) of the country.…”
Section: Introductionmentioning
confidence: 99%